Intracanal, intratubular antimicrobial evaluation and the ability to remove organic tissue with biomechanical preparation using instruments associated with endodontic ultrasonic inserts with final irrigation protocols in flattened canals - Conti, Leticia Citelli (2023)
Aim: To compare the ability of intracanal and intratubular decontamination and the removal of organic tissue with a modified biomechanical preparation method performed with endodontic instruments associated with ultrasonic tips, testing different final irrigation protocols by varying the irrigants in flattened canals. Material and methods: One hundred mandibular premolars and two hundred roots of bovine teeth were prepared, sterilized, and contaminated with Enterococcus faecalis (ATCC-29212). The human premolars were divided into a Control Group (CG: n=10), which did not receive any protocol, and into test groups according to the irrigating substance used: Saline Solution Group (SS: n=30), Sodium Hypochlorite Group (2.5% NaOCl: n=30) and Chlorhexidine Group (2% CHX: n=30). Canals were prepared with Reciproc® Blue 25/.08 (R25), Flatsonic®, Clearsonic® and Reciproc® Blue 40/.06 (R40). Each test group was divided into three subgroups (n=10), according to the established final irrigation protocol: Conventional Irrigation (CI), with syringe and needle; Passive Ultrasonic Irrigation (PUI) and Continuous Ultrasonic Irrigation (CUI), with Irrisonic® ultrasonic tip. Microbiological samples were taken from the pulp cavity of the premolars after using each biomechanical preparation instrument and the final irrigation protocol. These were cultivated to count the colony-forming units (CFU/mL). Roots of bovine teeth were randomly divided into 2 experimental groups (n = 100): with and without organic tissue inside the canal (CWT and CWOT). Each group was subdivided (n=10) according to the type of irrigant and based on the final irrigation protocol: Conventional Irrigation, with needle and syringe (CI), Continuous Ultrasonic Irrigation (CUI), and Passive Ultrasonic Irrigation (PUI). After carrying out the final irrigation protocol, all specimens were cleaved in a cutting machine, and samples of porcine palatine mucosa from the roots were collected and weighed after the completion of the tests. Canals were stained with Live/DeadLight to verify bacterial viability in confocal laser scanning microscopy. Data were collected, and analyzed, and specific statistical tests were applied to obtain the results (p<0.05). Results: All tested protocols considerably reduced both intracanal and intratubular contamination. Irrigants 2.5% NaOCl and 2% CHX were the most effective. CI was the least efficient in intracanal decontamination with saline solution. Activation of the irrigant resulted in greater intratubular decontamination and removal of intracanal organic tissue compared to non-activated groups. However, no method has eliminated all the biofilm from the canal, dentinal tubules, and organic tissue. Conclusions: The use of Flatsonic and Clearsonic ultrasonic tips in the biomechanical preparation associated with the activation of the irrigant in the final irrigation protocol seems to be promising in the disinfection of the flatted root canal, and the dentinal tubules. The final irrigation protocols considerably reduced the intracanal bacterial viability of the dentinal tubules and the amount of organic tissue using 24 mL of irrigant. Mechanical activation of the irrigants removed more organic tissue from the flattened root canals.